Efektifitas Pemberian Bueger Allen Exercise Dan Senam Kaki Terhadap Skor Ankle Brachial Index (ABI) Pada Pasien Diabetes Melitus Tipe II - riamah riamah; Anita Syarifah; Muhammad Irwan (LPPM Universitas Abdurrab, 2025)
One of the pillars in the management of diabetes mellitus is physical exercise. One of the physical exercises is the buerger allen exercise. Buerger allen exercise is one of the methods used to reduce the Ankle Brachial Index (ABI). The purpose of this study was to determine the effect of giving buerger allen exercise on Ankle Brachial Index (ABI) scores in type II diabetes mellitus patients at the Pandau Jaya Health Center. The research used in this study was pre-experimental, using the one group pre-test post-test method with paired T test. Data collection was carried out using observation sheets. The sample was determined by purposive sampling method of 20 respondents without a control group. Analysis was performed by univariate analysis and bivariate analysis using paired sample T test. The statistical test results obtained a p-value of 0.000 (P-value <0.005), so it can be concluded that there is an effect of giving buerger allen exercise on the Ankle Brachial Index (ABI) score in type II diabetes mellitus patients at the Pandau Jaya Health Center. It is suggested that the public can apply the Buerger Allen Exercise as one of the methods used to increase the Ankle Brachialindex Value